Fenofibrate Ameliorates Hepatic Ischemia/Reperfusion Injury in Mice: Involvements of Apoptosis, Autophagy, and PPAR-α Activation - Jie Zhang; Ping Cheng; Weiqi Dai; Jie Ji; Liwei Wu; Jiao Feng; Jianye Wu; Qiang Yu; Jingjing Li; Chuanyong Guo (PPAR Research)
Hepatic ischemia and reperfusion injury is characterized by hepatocyte apoptosis, impaired autophagy, and oxidative stress. Fenofibrate, a commonly used antilipidemic drug, has been verified to exert hepatic protective effects in other cells and animal models. The purpose of this study was to identify the function of fenofibrate on mouse hepatic IR injury and discuss the possible mechanisms. A segmental (70%) hepatic warm ischemia model was established in Balb/c mice. Serum and liver tissue samples were collected for detecting pathological changes at 2, 8, and 24 h after reperfusion, while fenofibrate (50 mg/kg, 100 mg/kg) was injected intraperitoneally 1 hour prior to surgery. Compared to the IR group, pretreatment of FF could reduce the inflammatory response and inhibit apoptosis and autophagy. Furthermore, fenofibrate can activate PPAR-α, which is associated with the phosphorylation of AMPK.